Kedudukan Hukum Anak Astra dalam Hukum Waris Adat Bali Setelah Orang Tua Biologisnya Kawin Sah - Agus Suarnegara; I Made Suwitra; I Ketut Sukadana (Jurnal Interpretasi Hukum, 2021)
The legal position of Astra's children in Balinese traditional inheritance law after their parents are legally married will follow their father. Many are found in community life, the incidence of children born to women who are not yet in a legal marriage bond so that it can cause problems. This study aims to explain the legal position of Astra's children after the enactment of Law Number 1 of 1974 concerning Marriage and to describe the inheritance rights of Astra's children in Balinese customary law after their biological parents are legally married. This study used normative research by examining the prevailing laws and regulations by relating the realities in the field, in this regard, of course, the right approach is the Legislative Approach. The legal materials used were primary and secondary legal materials. Furthermore, the collected legal materials are processed and analyzed using systematic interpretation analysis techniques. The results showed that the position of Anak Astra after the enactment of Law no. 1 of 1974, legally only has a civil relationship with his mother and his mother's family. The rights of Astra's children in Balinese customary law After their biological parents get married legally in Bali, it is after Astra's child is born in a legal marriage that his rights and status are according to his father (purusa).